Decisions under uncertainty in social contexts - Stephan Müller; Holger A. Rau (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2017)
This paper theoretically and experimentally studies decision-making in risky and social environments. We explore the interdependence of individual risk attitudes and social preferences in the form of inequality aversion as two decisive behavioral determinants in such contexts. Our model and the data demonstrate that individual risk aversion is attenuated when lagging behind peers, whereas it is amplified under favorable income inequality. Moreover, people's choices are not only contextdependent, but are sensitive to their degree of inequality aversion. The majority of our experimental findings cannot be rationalized by rank-dependent utility models or cumulative prospect theory. Our results contribute to the basic understanding of the underlying motives of private households' saving decisions, employees' careertrack choices or charitable giving under uncertainty.
http://hdl.handle.net/10419/146895
Keywords: C91; D03; D63; D81; 330; choice under uncertainty; social comparison; inequality aversion; risk preferences